Rifampicin Resistant Mycobacterium Tuberculosis in Nasarawa State, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:The diagnosis and treatment of drug resistant tuberculosis (TB) has presented a unique challenge to the control of TB in Nigeria. Various studies have reported the presence of drug resistant TB, and some treatment centres have been established to treat cases. This study sought to establish the prevalence of rifampicin-resistant TB in our state with a view to advocating for more commitment to efforts toward the treatment and control of drug-resistant TB, including establishment of more treatment centres in the geopolitical zone.Materials and Methods:A retrospective review of laboratory records of 1882 patients whose sputum samples were sent to the Gene Xpert Laboratory of our facility between January 2014 and April 2015 forMycobacterium tuberculosis(MTB) and rifampicin resistance assay was done using the Gene Xpert MTB/RIF assay. The patients were presumptive TB cases, suspected TB treatment failures, and suspected drug resistant cases from various health facilities in the state.Results:Of the 1882 patients, 68.4% were females and 36.6% were males; patients were aged between 1 and 70 years. MTB was detected in 18.8% (355/1882) of the patients. Forty-three of the 355 MTB positive patients were rifampicin resistant giving a prevalence of RIF resistance of 12.1%. A total of 62.8% of the RIF resistant cases were males whereas 37.2% were females. Forty-one percent of the RIF Resistant cases were aged between 21 and 30 years, 51.2% were human immunodeficiency (HIV) positive, 44.2% were HIV negative, whereas 4.6% had unknown HIV status. A higher number (62.8%) of those with RIF resistance were referred from other facilities compared to 37.2% from the host facility. There was significant association between RIF Resistance and sex, HIV status, and the facility.Conclusion:This study has established that there is a high prevalence of rifampicin resistance in the state. There is need to increase commitment to efforts being made towards treatment and control of DRTB in this zone.